2017
DOI: 10.18632/oncotarget.21329
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, prognosis and bioinformatics analysis of lncRNAs in hepatocellular carcinoma

Abstract: This study aims to comprehensively analyze the diagnosis and prognosis of lncRNAs in hepatocellular carcinoma (HCC). From the Gene Expression Omnibus database, we screened out and analyzed the differently expressed lncRNAs and related mRNAs using bioinformatics methods. The expressions of lncRNAs were validated in tumor tissues, cell lines and the Cancer Genome Atlas database. At the same time, we also conducted an exploratory analysis on the diagnostic and prognostic ability of lncRNAs in HCC. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 38 publications
3
41
0
Order By: Relevance
“…LncRNAs are a class of noncoding RNAs with lengths longer than 200 nucleotides, show no capacity of protein coding, but might regulate gene expression at genetic and epigenetic levels . So far, variety of lncRNAs or lncRNA groups have been uncovered might dictate HCC prognosis by multiple studies, most of which are about the functional roles and working mechanisms of single lncRNAs, and totally two (by Wang et al in 2017 and Ma et al in 2018) are found to describe the prognostic significance of multiple‐lncRNA signature in HCC . However, we should be wary of the conclusions of the previous studies for the following reasons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…LncRNAs are a class of noncoding RNAs with lengths longer than 200 nucleotides, show no capacity of protein coding, but might regulate gene expression at genetic and epigenetic levels . So far, variety of lncRNAs or lncRNA groups have been uncovered might dictate HCC prognosis by multiple studies, most of which are about the functional roles and working mechanisms of single lncRNAs, and totally two (by Wang et al in 2017 and Ma et al in 2018) are found to describe the prognostic significance of multiple‐lncRNA signature in HCC . However, we should be wary of the conclusions of the previous studies for the following reasons.…”
Section: Introductionmentioning
confidence: 99%
“…First, most previous studies screened out survival related lncRNAs based on the differential profile between cancer and noncancerous samples . The method could miss considerable survival information in The Cancer Genome Atlas (TCGA) datasets including some important prognostic genes, and lncRNAs as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 In intrahepatic cholangiocarcinoma cases, Xia et al indicated that CRNDE overexpression was obviously correlated with poor differentiation grade, present lymph node metastasis, advanced tumor-nodes-metastasis (TNM) stage, and large size. 35 The discrepancy between Chen et al's result and Dai et al's result would be most likely due to the different samples and method used. 23 In addition, similar results also were reported in bladder cancer cases.…”
Section: Discussionmentioning
confidence: 77%
“…34 However, Dai et al showed that there was no statistically association between CRNDE and clinicopathological characteristics in hepatocellular carcinoma. 35 The discrepancy between Chen et al's result and Dai et al's result would be most likely due to the different samples and method used. Thus, more studies would be needed to verify the clinical significance of CRNDE in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 77%